Upaya Pencegahan dan Pengendalian Leptospirosis Melalui Pendekatan Diagnosis Komunitas di Desa M, Kabupaten Tangerang, Banten, Indonesia - Amalia Riana; Dewi Novianti; Arie Akbar (KOLONI, 2026)
Leptospirosis is a zoonotic infection transmitted from infected animals through their urine, either directly or through contaminated soil or water. In 2025, the working area of Community Health Center K showed an increase in the number of leptospirosis cases accompanied by death, one of which was in Village M. The Community Diagnosis Program was carried out in an effort to identify problems and improve interventions. In the initial stage, problem priority was determined using the USG scoring method, followed by identification of the cause of the problem using the BLUM Paradigm. The Delphi non-scoring technique, Fishbone Diagram and the Five Whys methods were used to determine the root cause of the problem. Planning to evaluation of interventions were carried out by involving various related parties and outlined in the Log Frame Goal, POA, timeline, PDCA cycle and System Approach. Low community knowledge, an environment that is at risk of leptospirosis, and lack of support from the village are the main concerns as the cause of the high number of Leptospirosis cases in this village. The intervention in the form of outreach succeeded in increasing community knowledge by 66,25 points, the community actively participated in the mutual cooperation activities to clean the environment and established communication between the community health center doctors, village midwives, health cadres and village officials. The activities are expected to resolve the problems in Village M and support the long-term goal of preventing and controlling leptospirosis in the working area of Community Health Center K.